THE EFFECT OF BED HEAD ELEVATION IN PREVENTING VENTILATOR-ASSOCIATED PNEMONIA (VAP) IN PATIENTS ON VENTILATION - Sutrisno; Dian Sari Maharani; Mayta Sari Dwianggimawati (Nursing Sciences Journal, 2025)
Ventilator Associated Pneumonia (VAP) is a common nosocomial infection in patients using ventilators. One recommended prevention method is head elevation of bed (HoB) at a 30-45 degree angle. The purpose of this study was to analyze the effect of head elevation on VAP prevention in patients on ventilators in the ICU of Dr. Iskak Tulungagung Regional Hospital. This study used a pre-experimental design. The sample consisted of 20 patients selected by consecutive sampling. Data were collected through Clinical Pulmonary Infection (CPIS) observations before and after the intervention for three days. The results showed that of the 20 patients who received the HoB intervention, 75% did not experience VAP, while 25% continued to experience VAP. The CPIS value increased significantly on the second and third days, indicating that this period is a critical phase for VAP development. Elevating the HoB position has an effect on reducing the risk of VAP, but does not completely prevent infection. Effective VAP prevention requires a comprehensive approach that combines HoB with other measures such as oral hygiene, endotracheal cuff pressure monitoring, and optimal ventilation management.   Keywords: Head elevation of bed (HoB), Pneumonia, Ventilator.